Mekanisme Pengangkatan dan Pemberhentian Perangkat Desa Perspektif Fiqih Siyasah Tanfidziyah - Delfi Wulandari; Supardi; Abdul Hafiz (CV. Doki Course and Training, 2024)
This study aims to analyze the impact of the mechanism for the appointment and dismissal of Village Apparatus that is not in accordance with the Regulation of the Regent of South Bengkulu Number 09 of 2019 concerning Procedures for the Appointment and Dismissal of Village Apparatus, especially in Penindaian Village, Kedurang Ilir District, South Bengkulu Regency. In addition, this study also examines the mechanism from the perspective of fiqh siyasah tanfidziyah as the basis for Islamic law relating to governance. The type of research used in this study is field research. Data collection uses observation, interview and documentation techniques. This study found that the mechanism for the appointment and dismissal of Village Apparatus in Penindaian Village, Kedurang Ilir District, South Bengkulu Regency, which is not in accordance with the Regulation of the Regent of South Bengkulu Number 09 of 2019, has had significant legal and social impacts. In addition, the mechanism does not fulfill the principles of fiqh siyasah tanfidziyah, such as equality, brotherhood, accountability, tolerance, freedom, deliberation, justice, balance, moderation, and obedience. The results of this study highlight the importance of enforcing regulations and implementing fiqh siyasah values ​​in village governance to achieve justice and harmony in society.